Englishmen transplanted the English colonization of Barbados, 1627-1660 - Gragg, Larry Dale, 1950- (Oxford University Press, 2003)
This volume challenges the widely accepted view of 17th-century Barbados planters as reckless fortune seekers who failed to create a viable society in the tropics. Rather, it argues they were settlers eager to transplant what was familiar to them.